2018
DOI: 10.1021/acs.jafc.8b00819
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced S-Adenosylmethionine Production by Increasing ATP Levels in Baker’s Yeast (Saccharomyces cerevisiae)

Abstract: In the biosynthesis of S-adenosylmethionine (SAM) in baker's yeast ( Saccharomyces cerevisiae), ATP functions as both a precursor and a driving force. However, few published reports have dealt with the control of ATP concentration using genetic design. In this study we have adopted a new ATP regulation strategy in yeast for enhancing SAM biosynthesis, including altering NADH availability and regulating the oxygen supply. Different ATP regulation systems were designed based on the introduction of water-forming … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 43 publications
0
32
0
Order By: Relevance
“…In addition to erythromycin production, the cell growth, maintenance, intracellular environment control, substrate transport, and product export also require an adequate supply of ATP. 52 For instance, increasing ATP levels in baker's yeast enhanced biosynthesis of Sadenosylmethionine, 31 which is one of the essential precursors for erythromycin production in S. erythraea. Our results extend our knowledge about the correlation between energy level and antibiotic production in accordance with some previous research.…”
Section: Overexpression Of F 1 -Atpase Alters the Electronmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to erythromycin production, the cell growth, maintenance, intracellular environment control, substrate transport, and product export also require an adequate supply of ATP. 52 For instance, increasing ATP levels in baker's yeast enhanced biosynthesis of Sadenosylmethionine, 31 which is one of the essential precursors for erythromycin production in S. erythraea. Our results extend our knowledge about the correlation between energy level and antibiotic production in accordance with some previous research.…”
Section: Overexpression Of F 1 -Atpase Alters the Electronmentioning
confidence: 99%
“…When the soluble F 1 part is free from the membrane, it hydrolyzes ATP to ADP and it is therefore possible to alter the intracellular [ATP]/[ADP] ratio by changing the expression of the F 1 part of the F 1 F 0 -ATPase. , In fact, by tuning the expression of F 1 -ATPase, researchers found that the glycolysis could be uncoupled from biomass production without primary effects on other cellular processes . However, the earlier studies have focused solely on the effects on primary metabolism in E. coli and L. lactis , , and less attention has been paid to organisms with extensive secondary metabolic routes.…”
mentioning
confidence: 99%
“…The positive effect of SAM on pesticide metabolism in crops is worth exploring. SAM is a safe and versatile dietary supplement . Due to its safety and its role in a diverse range of biological functions, we propose that SAM could be used to promote plant degradation of pesticides.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, enzymes and ATP are continuously generated during fermentation in living cells, which is more conducive to the synthesis of products by energy-consuming pathways (Y. Chen & Tan, 2018;Singh et al, 2011;R. Xu et al, 2018).…”
Section: Hatzimanikatismentioning
confidence: 99%
“…However, it cannot be continuously and efficiently supplied by the permeabilized cells because the treated cells fail to produce enzymes, and, therefore, the residual enzyme activities are gradually reduced (Y. Chen & Tan, 2018; Singh, Soh, Hatzimanikatis, & Gill, 2011; R. Xu, Wang, Wang, Zhang, & Wei, 2018). In contrast, enzymes and ATP are continuously generated during fermentation in living cells, which is more conducive to the synthesis of products by energy‐consuming pathways (Y. Chen & Tan, 2018; Singh et al, 2011; R. Xu et al, 2018). Intracellular ATP is a key limiting factor for CDP‐choline biosynthesis, but the feeding of exogenous ATP is not economical for industrial applications.…”
Section: Introductionmentioning
confidence: 99%